√6 multiply with √27 is equal to

Answer: √6 × √27 = 9√2

√6 × √27

The given problem can be solved by expressing each term into individual roots and multiplying

How can we express √6?

√6 can be expressed as

√6 = √2 × √3

How can we express√27?

√27 = √(3 × 3 × 3)

√27 = √(3) ×√(3)2

√27 = 3√3

√6 × √27 = √2 × √3 × 3√3

√6 × √27 = √2 × √3 × √3 × √3 × √3

√6 × √27 = 3 × 3√2

√6 × √27  = 9√2

Answer

√6 × √27 = 9√2

Articles to Explore:

  1. Find the value of (16)3/4?
  2. Without adding, find the sum. (i) 1 + 3 + 5 + 7 + 9 (ii) 1 + 3 + 5 + 7 + 9 + 11 + 13 + 15 + 17 +19 (iii) 1 + 3 + 5 + 7 + 9 + 11 + 13 + 15 + 17 + 19 + 21 + 23

Was this answer helpful?

 
   

4.5 (48)

(157)
(28)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published.

*

*

close
close

DOWNLOAD

App Now

Ask
Question